Nocturnal Cooling of Water as Free Cooling Source for Building Indoor Radiant Cooling in Malaysian Climate - Muhammad Syukri Imran, Abdullah; Azhaili, Baharun; Siti Halipah, Ibrahim; Wan Azlan, Wan Zainal Abidin (Trans Tech Publications, Ltd, 2016)
Normally mechanical chiller supplies chill water temperature at a higher operating temperature to charge a radiant cooling system in building. Other source of cooling is possible since the operating temperature for radiant cooling is limited by the air dew point temperature. This study investigates cooling of water through long wave radiation to the night sky in Kuching Sarawak, Malaysia and utilise this water for radiant cooling purpose. Mathematical model were developed to predict the cooling power of the nocturnal cooling over typical metal roof and was compared to an experimental data. The measurement from the test model verified the predicted data and a yearly potential from nocturnal cooling in this region was established. The amount of cooled water generated from this night cooling system was also calculated. Results showed that an average of 73 W/m2 nocturnal cooling power is possible in this region.